Effect of Glucose Concentration on the Production of Proteolytic Extract by Different Strains of Aspergillus under Solid-State Fermentation - Liliana Londoño-Hernández; María de Jesús García-Gómez; Sergio Huerta-Ochoa; Anna María Polanía-Rivera; Cristóbal Noé Aguilar; Lilia Arely Prado-Barragán (Fermentation, 2024)
Proteases are important enzymes because of their extended uses in several industries, such as food, beverages, pharmacy, detergents, and many others. Aspergillus is one of the most used fungi strains for enzyme production by solid-state fermentation (SSF). Disponibility of the carbon source is a key factor for protease production. In addition, the selection of solid support has great importance, as it must provide suitable airflow through the packed bed and nutrient diffusion inside the fermentable mass. Six Aspergillus strains and two inert supports (Agrolite (AL) and Polyurethane (PUF)) were tested for protease production from fish flour (FF) at different glucose concentrations (0, 5, 10, 15%) by SSF. The FF/PUF mixture at 70/30 (w/w) ratio, with 75.39% moisture, and a critical moisture point of 0.11 gH2O/g, presented a texture that allowed heat and mass transfer and provided enough moisture to make free water available as required for microorganism growth during the fermentation process. Aspergillus oryzae 2095 produced higher amounts of neutral and alkaline proteases with the addition of 5% glucose to the growth medium. Kinetics studies reveal that protease production is partially associated with growth. The extracts obtained can be used in different industries, and especially to prepare fish high-value by-product hydrolysates.